PENGARUH ARUS KAS, STRUKTUR MODAL DAN OPERATING CAPACITY TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MAKANAN DAN MINUMAN DI INDONESIA TAHUN 2018-2021 - Sri Retnoningsih; Fajar Wulaningsih (Bisnis-Net, 2023)
This research is motivated by the global economic crisis and multidimensional crisis triggered by the co-19 pandemic. Debt vulnerability and its effects on the economy might worsen if global economic difficulties persist. Because of this, the business may have trouble meeting its debt obligations and may ultimately fail and is in danger of being dissolved. The purpose of this study is to empirically explore the influence of cash flow, capital structure, and operational capacity in the setting of financial hardship. The 112 studies covered the years 2018 through 2021 and included a sample size of 28 food and beverage producers trading on the Indonesia Stock Exchange. All of the information for this research came from a planned selection of participants. The data in this study was analysed using a multiple linear regression model in SPSS Version 25. As a stand-in for Financial Distress, we employed the Almant Z-Score technique. This study demonstrated that a number of factors significantly impacted financial hardship, including cash flows from operating operations, cash flows from investment activities, cash flows from financing activities, capital structure, and operational capabilities. Cash flow from operating activities and operating capacity are positively and significantly related to financial stress. Financial stress is mostly caused by insufficient investment cash flow, insufficient financing activity cash flow, and insufficient capital structure.